Diagnostics of the Origin of Encephalitis and Modern Clinical Diagnostics (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Encephalitis is a life-threatening inflammation of the brain that can be caused by viruses or bacteria or as a serious complication of other diseases. Encephalitis is often caused by infections that are transmitted to humans from others or through the bites of ticks, mosquitoes, and other blood-sucking animals.